ENGLISH TEACHERS TEACHING STRATEGIES AND STUDENT'S PERCEPTIONS ON THEIR TEACHERS’ STRATEGIES USED IN ONLINE LEARNING - Syahrir, Masitha Syahrani; Jabu, Baso; Baa, Sultan (State University of Makassar, 2022)
The aims of this study were to find out the strategies used by English teachers during online learning at SMPN 1 Maros and to discover students’ perception to teacher teaching strategy used in online learning. The research design in this study was qualitative method and data collected through questionnaires and interviews. The subjects of this study were English teachers and students at SMPN 1 Maros. The sample of the questionnaire was 45 students were selected using technique purposive sampling and interviews of three English teachers and six students were taken using technique purposive sampling. The results of this study showed that (1) there were a number of strategies used by English teachers during online learning including using video media in the form of a link from YouTube, discuss and ask through application WhatsApp, using image media in the form of posters, gifts module, and through zoom meeting app. Next in arranged learning designs, all teachers did not involve student in the arrangement but they the one who composes and designs method learning that will used during the learning process teach, (2) there were a number of perception student to strategy teaching used by the teacher during online learning, among others, perception student show response positive to strategy teaching English teacher. English Teacher already very good in prepare and deliver Theory as well as enjoy the learning process though held online and the teacher has also supported with means adequate infrastructure.Keywords - Students perception, teaching strategy, online learning.